PENGUKURAN JARING KONTROL HORIZONTAL PADA PROYEK PEMBANGUNAN BENDUNGAN CIPANAS - Sumarna, Nana; Gustawan, Tatang (Universitas Majalengka, 2019)
The more rapid economic development, the more rapid the development of infrastructure. In civil engineering, one of the sciences studied is land surveying. In this case it is intended not only to measure land alone, but can be broadly developed, that is, mapping things according to the originals. In a construction for example the measurement of the position of the excavation of the foundation, and measurement of other structures both horizontally and vertically. For performers construction measurements are the main requirements that must be owned, because when the size is wrong, the results will be wrong. Construction actors are those who are involved in it, from those who plan it and also those who carry it out, from unskilled laborers to work leaders, measuring using simple tools or using modern tools that will further accelerate the results of work. So in civil engineering at Majalengka University, it was learned how to measure flat and detailed measurements using automatic level, theodolite, and total station. Measurement techniques are studied in soil surveying practicum subjects. In the world of professional work, measurement workers are called Surveyors. The more sophisticated the measuring instrument, the faster the task is completed. Majalengka University Civil Engineering Study Program at the beginning of the seventh semester did job training. It was then that the author had the opportunity to forge deeper geometry as well as practical work on the Cipanas Dam Construction Project.